Methodological Considerations for Identifying Questionable Publishing in a National Context – the Case of Swedish Higher Education Institutions - data - Nelhans, Gustaf (University of Borås, 2020)
The overall scope of this study is an attempt at a methodological framework for matching publication lists at the national level against a combined set of blacklists for questionable publishing. Using the total verified set of publications from Swedish Higher Education Institutions (HEI) as a case, we examined the number, distribution, and proportion of publishing in questionable journals at the national level. Supplemental data, as well as the raw matched data so that tables and figures in the article can be reproduced. Additionally, a list of all matched outlets, along with the total number of matched articles are presented here. Publication data is matched at journal level against HEIs. No article ids are provided in the data set.

Supplemental data, as well as the raw matched data so that tables and figures in this article can be reproduced.

Studiens övergripande syfte är att skapa en metodologiskt ramverk för att matcha publikationslistor på nationell nivå mot en kombinerad uppsättning svartlistor för misstänkt tvivelaktig publicering. Med hjälp av den totala verifierade uppsättningen av publikationer från svenska högskolor som fall undersökte vi antalet, fördelningen och andelen publicering i misstänkt tvivelaktiga tidskrifter på nationell nivå. Kompletterande data, liksom råmatchade data så att tabeller och figurer i artikeln kan reproduceras tillgängliggörs här. Vidare presenteras en lista över alla matchade publikationskanaler, tillsammans med det totala antalet matchade artiklar. Publikationsdata matchas på tidskriftsnivå mot författarnas lärosätestillhörighet. Inga artikel-id finns i datauppsättningen.

Underliggande data för att producera tabeller och figurer i studien.
Methodological considerations for identifying Questionable Publishing in a National Context – the case of Swedish Higher Education Institutions - Metodologiska överväganden för att identifiera tvivelaktig publicering i nationellt sammanhang - fallet med svenska högskolor - data
Keywords: questionable publishing; tveksam publicering; publication ethics; publiceringsetik; publication blacklists; svarta listor över publikationer; Higher and further education; Gymnasial och högre utbildning; Information technology; Informationsteknik; Other Social Sciences not elsewhere specified; Övrig annan samhällsvetenskap; Ethics; Etik; Information Studies; Biblioteks- och informationsvetenskap